Blacklisted - Crownover, Jay (Crownover, Jay. Loveless, Texas novel, 2020)
"Dr. Presley Baskin has always lived a quiet, calm life. Unfortunately, nothing about her life in Loveless, Texas -- especially not the wild, rowdy, and impossibly close-knit Lawton family who've claimed her -- is quiet or calm. Which is how loner Presley finds herself roped into patching up local bad boy Shot Caldwell against her better judgment. Presley wants nothing to do with the dangerous, brooding leader of the local outlaw motorcycle club. But when someone starts stalking her, Shot is the only person she trusts to help. Plus he owes her one. . . Palmer 'Shot' Caldwell has always known his life isn't made for relationships. At least until shy, secretive, Presley reluctantly pulled a bullet out of him. He's oddly protective of the pretty doctor, so when she comes to him for help, hard-hearted Shot suddenly realizes there's nothing he wouldn't do to keep her safe."--Provided by publisher.